Uma proposta de trabalho com a concordância de número em textos de alunos do Ensino Fundamental II - Ribeiro, Simone Cristina Palota (2020)
In this dissertation, wereport a research carried out with the aim to investigate the realization of noun and verb number agreement in texts of students atElementary School II in a state school in Esperança Nova (Paraná, Brazil), as wellasto developa project of classroom intervention, by applying a didactic unit aimed at improving the student’s language skills in writing and minimizingthe occurrence of non-standard agreement. It was a qualitative interpretivist, ethnographic-based research, because it was carried out in the school environment. As there was intervention in the classroom, we used action research as amethodological procedure. As a theoretical framework, we were based especially on Educational Sociolinguistics, which provides elements to reflect on the phenomenon of language variation, whose implications are manifested in the transposition of oral to written language and reflected in the classroom. For the description and analysis of cases of non-standard verb and noun agreement, specifically, we sought theoretical support in the studies of Variationist Sociolinguistics researchers’ scale, especially regarding the linguistic variables phonic salienceand precedent marks. In the elaboration of the didactic unit, we decided to approach the re-textualization of the textual genre personal report that culminated in the Collection of reports from Esperança Nova. The results of the classroom intervention indicated that, in fact, the students presented persistent difficulties regarding marking, in writing, the number agreement, especially when the phonic salience is minimal, although we observed a better performance after the intervention in comparison with the initial data.